Adhesion of Helicobacter Species to the Human Gastric Mucosa: A Deep Look Into Glycans Role - Matos, Rita; Amorim, Irina; Magalhães, Ana; Haesebrouck, Freddy; Gärtner, Fátima; Reis, Celso A. (Frontiers in Molecular Biosciences, 2021)
Helicobacter species infections may be associated with the development of gastric disorders, such as gastritis, peptic ulcers, intestinal metaplasia, dysplasia and gastric carcinoma. Binding of these bacteria to the gastric mucosa occurs through the recognition of specific glycan receptors expressed by the host epithelial cells. This review addresses the state of the art knowledge on these host glycan structures and the bacterial adhesins involved in Helicobacter spp. adhesion to gastric mucosa colonization. Glycans are expressed on every cell surface and they are crucial for several biological processes, including protein folding, cell signaling and recognition, and host-pathogen interactions. Helicobacter pylori is the most predominant gastric Helicobacter species in humans. The adhesion of this bacterium to glycan epitopes present on the gastric epithelial surface is a crucial step for a successful colonization. Major adhesins essential for colonization and infection are the blood-group antigen-binding adhesin (BabA) which mediates the interaction with fucosylated H-type 1 and Lewis B glycans, and the sialic acid-binding adhesion (SabA) which recognizes the sialyl-Lewis A and X glycan antigens. Since not every H. pylori strain expresses functional BabA or SabA adhesins, other bacterial proteins are most probably also involved in this adhesion process, including LabA (LacdiNAc-binding adhesin), which binds to the LacdiNAc motif on MUC5AC mucin. Besides H. pylori, several other gastric non-Helicobacter pylori Helicobacters (NHPH), mainly associated with pigs (H. suis) and pets (H. felis, H. bizzozeronii, H. salomonis and H. heilmannii), may also colonize the human stomach and cause gastric disease, including gastritis, peptic ulcers and mucosa-associated lymphoid tissue (MALT) lymphoma. These NHPH lack homologous to the major known adhesins involved in colonization of the human stomach. In humans, NHPH infection rate is much lower than in the natural hosts. Differences in the glycosylation profile between gastric human and animal mucins acting as glycan receptors for NHPH-associated adhesins, may be involved. The identification and characterization of the key molecules involved in the adhesion of gastric Helicobacter species to the gastric mucosa is important to understand the colonization and infection strategies displayed by different members of this genus.